IMPLEMENTASI AKAD ISTISHNA TERHADAP JUAL BELI FURNITURE (STUDY DI RASYID MEUBEL KABUPATEN TAKALAR) - risma, rismayanti; Amiruddin, Amiruddin; Sirajuddin, Sirajuddin (Investama : Jurnal Ekonomi dan Bisnis, 2023)
The development of traditional patterns to modern patterns in the buying and selling process has occurred in people's lives. Human life is increasingly developing in various fields, as well as in industrial activities. If viewed from the needs of the community, one of the areas of interest is the furniture business. In the current process of buying and selling furniture, consumers order according to the specifications of the goods they want. However, after making an agreement between the seller and the buyer, the contract that has been implemented has not been carried out as desired due to obstacles such as the cancellation of the agreed contract between the two. Cancellations made will have an impact on the seller because it will be detrimental, the goods that have been made are now left and displayed but the goods are difficult for other people to buy because they do not match expectations with the specific goods desired, therefore, the seller must improve the way of marketing his goods so that buyers are interested want to buy it. This study aims to find out, understand and explain the cancellation of the istishna contract for the sale and purchase of furniture and the completion of the cancellation of the istishna contract for the sale and purchase of furniture at Rasyid Furniture. The type of research used is a qualitative method. The data analysis techniques include data reduction, data presentation, data editing, data analysis and drawing conclusions. The results of the study explain that 1. The practice of canceling istishna contracts for buying and selling furniture at Rasyid Furniture focuses on the causes of delays in financing. There was an extravagant attitude when the execution of the contract was in progress or for other reasons such as the party falling bankrupt which resulted in no longer having power over the assets that became valid in the contract 2. Completion of the cancellation of the istishna contract for buying and selling at Rasyid Furniture in a peaceful way such as providing some facilities to be able to pay partial down payment and can be paid off when the goods are delivered to the buyer's house.